A Case Report of Reverse Split-hand Syndrome: An Overlooked Clinical Sign of Hirayama Disease - Saha, Sujan; Rahman, Hasan Zahidur; Islam, Md Rafiqul; Alam, SK Mahbub; Al Muzahid, Md Abdullah; Chowdhury, Ashish; Hasan, Mehedi; Roy, Uttam; Kabir, Md Suman (Bangladesh Journal of Neuroscience, 2019)
Hirayama disease (HD) is considered to be a relatively benign, slowly progressive and less disabling rare neurological disorder where flexion induced compressive ischemic lower cervical myelopathy causes selective anterior horn cell injury resulting weakness and atrophy of distal upper limb without any pyramidal, spinothalamic and posterior column disturbance. Herein, we report a young male with clinical and imaging features suggestive of Hirayama disease presented with dissociated hand muscle atrophy (hypothenar more affected than thenar) in both hands. This less recognized finding was previously termed as reverse split-hand syndrome just opposite to split-hand syndrome found in amyotrophic lateral sclerosis. We also observe electrophysiological correlation of reverse split-hand syndrome in HD. Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 110-114